2021
DOI: 10.1021/acsnano.0c09732
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity of Cationic Ligands Promotes Irreversible Adsorption of Nanoparticles to Lipid Bilayers

Abstract: A mechanistic understanding of the influence of the surface properties of engineered nanomaterials on their interactions with cells is essential for designing materials for applications such as bioimaging and drug delivery as well as for assessing nanomaterial safety. Ligand-coated gold nanoparticles have been widely investigated because their highly tunable surface properties enable investigations into the effect of ligand functionalization on interactions with biological systems. Lipophilic ligands have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…21,22 Additionally, QCM has been extensively employed to study discrete adsorbates such as abiotic and biological macromolecules and nanoparticles (NPs). These studies included investigations of biomolecular interactions of proteins 23,24 and viruses; 25,26 structure, 27,28 confirmation 29,30 and orientation changes 31 of biomacromolecules; spatial distribution, 32 size, 33−35 deformation 36,37 and dissolution 38 of NPs; protein corona formation on amyloids; 39 interactions between NPs and biomimetic membranes; 40,41 as well as bioanalytical sensor development. 42−46 Yet, the inseparable nature of the adsorbate and liquid contributions to the measured response puts a significant limitation on quantitative interpretation of adsorption measurements in a liquid environment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Additionally, QCM has been extensively employed to study discrete adsorbates such as abiotic and biological macromolecules and nanoparticles (NPs). These studies included investigations of biomolecular interactions of proteins 23,24 and viruses; 25,26 structure, 27,28 confirmation 29,30 and orientation changes 31 of biomacromolecules; spatial distribution, 32 size, 33−35 deformation 36,37 and dissolution 38 of NPs; protein corona formation on amyloids; 39 interactions between NPs and biomimetic membranes; 40,41 as well as bioanalytical sensor development. 42−46 Yet, the inseparable nature of the adsorbate and liquid contributions to the measured response puts a significant limitation on quantitative interpretation of adsorption measurements in a liquid environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Still, the rich information contained in combined Δ f n and Δ D n measurements, especially when complemented with theoretical models representing the response for viscoelastic films, has turned out to be very valuable in multiple research areas, including hydration analysis of organic polymers, , proteins, and biological membranes. , QCM has also been widely applied to monitor and characterize thin films, including porosity determination, , monitoring the growth of mesoporous materials, probing responsiveness of polymeric coatings, and characterization of biomimetic membranes. , Additionally, QCM has been extensively employed to study discrete adsorbates such as abiotic and biological macromolecules and nanoparticles (NPs). These studies included investigations of biomolecular interactions of proteins , and viruses; , structure, , confirmation , and orientation changes of biomacromolecules; spatial distribution, size, deformation , and dissolution of NPs; protein corona formation on amyloids; interactions between NPs and biomimetic membranes; , as well as bioanalytical sensor development. …”
Section: Introductionmentioning
confidence: 99%
“…15 The cascading effect of engineered NP properties on membrane attachment through dictating protein assemblage was elucidated by Melby et al 16 Recently, Lochbaum et al tuned the lipophilicity of cationic ligands on NPs and demonstrated its promotion to irreversible NP binding to supported lipid bilayers. 17 Using a complementary experimental and computational method, Tollefson et al determined the relative orientation of peripheral membrane proteins on functionalized NPs, 18 and proved its facilitating role in nanoparticle binding to model cell membranes. 19 Other properties, such as surface charge and chirality, were also found to modulate protein adsorption and conformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to the large surface-to-volume ratio, nanoparticles (NPs) acquire coatings of biomolecules, such as proteins and natural organic matter (NOM), upon entering an aquatic environment. Often referred to as the ecocorona, such molecular coating endows NPs with a new surface identity influencing NP behaviors at environmental and biological interfaces. Continuous efforts have been made to understand biomolecular adsorption on various NPs and its downstream impacts on NP attachment to cell membranes, often using solid-supported lipid bilayers as model systems. One previous study showed a lower amount of fullerene accumulated in supported lipid bilayers when adsorbed with humic acid (HA) due to surface modification of fullerene and the steric repulsion with the membrane . Mensch et al found effective binding of functionalized diamond NPs to the supported lipid bilayer only at lower NOM-to-NP ratios, as ascribed to changes in the hydrodynamic and electrokinetic properties by forming coronas .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is proposed that a drug delivery system that can transport DOX to the tumor site should be developed to achieve better antitumor effect and reduce adverse reactions. Due to the advantages that traditional delivery systems do not have, nano-drug delivery systems have been widely studied as drug carriers, and many nano-drug delivery systems have been developed, such as magnetic nanoparticles ( Hosseinpour Moghadam et al, 2019 ), microemulsion ( Lv et al, 2018 ; Wang et al, 2019 ), liposomes ( Antimisiaris et al, 2021 ), gold nanoparticles ( Lochbaum et al, 2021 ), platinum nanoparticles ( Kawawaki et al, 2021 ), polymer micelles ( Yang et al, 2021 ), etc. In these drug delivery systems, polymeric micelles are considered to be effective nanocarriers because they can encapsulate hydrophobic agents into their “core-shell” structures and deliver them to tumor regions through enhanced permeability and retention (EPR) effect.…”
Section: Introductionmentioning
confidence: 99%